Exterior of an ancient structure denominated in various records King John's Palace, with part of the Adam and Eve Coffee Rooms - Wise, William; Carter, James (Tufts Archival Research Center, 2008)
This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.